Transvenous microguidewire looping technique for breach of ipsilateral inferior petrosal sinus occlusions en route to cavernous sinus dural arteriovenous fistulas. Issue 5 (October 2016) - Cho, Young Dae; Rhim, Jong Kook; Yoo, Dong Hyun; Kang, Hyun-Seung; Kim, Jeong Eun; Cho, Won-Sang; Han, Moon Hee
Background and purpose: Transarterial access to dural arteriovenous fistulas (dAVFs) has been popularized by device improvements and novel embolic materials. However, this approach is limited in the cavernous sinus (CS) because of related complications and low cure rates. Although a transvenous approach, via ipsilateral inferior petrosal sinus (IPS), may be more suitable for CS-dAVFs, microcatheter delivery is occasionally impeded by ipsilateral IPS occlusion. Described herein is a microguidewire looping method to breach such occlusions, thus enabling access to CS lesions. Methods: A microcatheter is initially advanced into the IPS orifice, and a microguidewire is passed into the occluded IPS. Looping is easily achieved through the resistance met. With greater support of the guiding catheter, the microguidewire (still looped) is then advanced into the CS. When nearing the CS, the microcatheter is further reinforced, and it is navigated along the microguidewire into the CS. Results: This technique was applied in 10 instances of CS-dAVF with ipsilateral IPS occlusion, enabling ipsilateral access to the CS. In eight cases (80%), microdevice advancement was successful, culminating in effective transvenous coil embolization. Clinical and radiologic outcomes in all patients were excellent, with no delayed post-procedural cranial palsies. Conclusion: This microguidewire looping technique enables safe and effective entry into the CS during transvenous coil embolization of CS-dAVFs with ipsilateral IPS occlusion.